Microsoft Office 2013 quicksteps - Matthews, Carole Boggs; Matthews, Martin S.; Sandberg, Bobbi (QuickSteps., 2013)
Full color screenshots on every page with clear instructions help start using the latest release of the leading productivity suite of applications. Shows how to produce Word documents, create Excel spreadsheets, manage Outlook e-mail; and generate PowerPoint presentations.